JBRMR 2017
DOI: 10.24052/jbrmr/v11is04/aeaosimimsm
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of sectoral indices movement in Malaysian stock market

Abstract: The aim of this study is to investigate the dynamic movement between sectoral indices in the Malaysian Stock Market and the three macroeconomic variables, namely oil price (OP), gold price (GP), and exchange rate (ER) during the period 1995-2014. Using the Augmented Dickey-Fuller and Phillip Perron unit root test, the underlying series are tested as non-stationary at the level but stationary in first difference. The use of Johansen-Juselius (1990) Multivariate Cointegration and Vector Error Correction Model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Thus, this finding is conformity with the hypothesis of the market model and CAPM. This finding is also in line with findings of the extant studies that related to Malaysian sectoral equity analysis (Jafarian & Safari, ; Law & Ibrahim, ; Pyeman & Ahmad, ).…”
Section: Empirical Analysis and Discussionsupporting
confidence: 91%
“…Thus, this finding is conformity with the hypothesis of the market model and CAPM. This finding is also in line with findings of the extant studies that related to Malaysian sectoral equity analysis (Jafarian & Safari, ; Law & Ibrahim, ; Pyeman & Ahmad, ).…”
Section: Empirical Analysis and Discussionsupporting
confidence: 91%
“…These results are similar to those in the study on the Indian stock market, in which Minimol and Makesh (2017) found that the main indices, BSE Sensex and CNX Nifty, were stationary at first difference. Moreover, other sectoral indices in the NSE (India) market were also stationary at the first difference (Pyeman & Ahamad, 2017). Table 4 exhibits the results of the Johansen cointegration test between the PSEi and the six sectoral indices.…”
Section: Descriptive Resultsmentioning
confidence: 96%
“…Fama (1970) shared his work on unpredictability when he investigated the daily price changes of the Dow Jones Industrial Average in the US during the period 1957-1962. Over the past few decades, several academic scholars and financial market experts have been focusing their attention on modelling stock movements, particularly through stock indices. Generally, studies link stock indices with macroeconomic variables (Basci & Karaca, 2013;Pyeman & Ahamad, 2017). Forecasting the movement of stock prices is deemed to be one of the main problems of every investor and fund manager.…”
Section: Introductionmentioning
confidence: 99%